2020
DOI: 10.1111/bph.15330
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of suppressor of cytokine signalling 1‐based therapy in experimental abdominal aortic aneurysm

Abstract: Background and Purpose: Abdominal aortic aneurysm (AAA) is a multifactorial disease characterized by chronic inflammation, oxidative stress and proteolytic activity in the aortic wall. Targeting JAK/signal transducer and activator of transcription (JAK/STAT) pathway is a promising strategy for chronic inflammatory diseases. We investigated the vasculo-protective role of suppressor of cytokine signalling-1 (SOCS1), the negative JAK/STAT regulator, in experimental AAA. Experimental Approach: A synthetic, cell pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…It is estimated that the mortality rate is up to 90% upon AAA rupture [ 18 ]. Open and endovascular aneurysm repair surgery are the main therapeutic strategies for AAA; however, they are not applicable for small AAA (<rmsep 55 mm in diameter) [ 19 ]. Additionally, there is currently no effective pharmacotherapy available for AAA treatment [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that the mortality rate is up to 90% upon AAA rupture [ 18 ]. Open and endovascular aneurysm repair surgery are the main therapeutic strategies for AAA; however, they are not applicable for small AAA (<rmsep 55 mm in diameter) [ 19 ]. Additionally, there is currently no effective pharmacotherapy available for AAA treatment [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…For in vivo inhibition of Syk kinase, WT mice were treated with Bay 61‐3606 (S7006, Selleckchem; 50 mg/kg body weight, intraperitoneally, 3 days per week). Dose and administration route were chosen based on the previous literature 32 . For preventive treatment, mice ( n = 7) received Bay 61‐3606 for a period of 2 weeks (from day −1 until day 14 postperfusion).…”
Section: Methodsmentioning
confidence: 99%
“…Dose and administration route were chosen based on the previous literature. 32 For preventive treatment, mice (n = 7) received Bay 61-3606 for a period of 2 weeks (from day −1 until day 14 postperfusion). For therapeutic treatment, mice (n = 5) received Bay 61-3606 for 1 week (from day 7 until day 14 postperfusion).…”
Section: Adoptive Transfer and Syk Inhibition In Vivomentioning
confidence: 99%
“…On the basis of previous mutational studies, several research groups carried out numerous studies where they demonstrated that the linear peptide spanning KIR domain (52–67) inhibits/reduces 1) the activation of STAT by cytokines Th1 and 17 in leukocytes; 2) the activation and migration of vascular cells and macrophages in vitro ( Ahmed et al, 2015 ); 3) the expression of cytokines with pro-inflammatory properties in atherosclerotic plaques ( Recio et al, 2014 ); 4) the renal inflammation, oxidative stress, and fibrosis ( Recio et al, 2017 ; Lopez-Sanz et al, 2018 ; Opazo-Ríos et al, 2020 ); 5) the chronic intraocular inflammatory disease (as uveitis) ( He et al, 2016 ; Recio et al, 2017 ; Ahmed et al, 2018 ) [very recently, in equine recurrent uveitis (ERU), that is, the only spontaneous model of human recurrent uveitis ( Larkin et al, 2020 )]; 6) the inflammation in the abdominal aortic aneurysm (AAA), to downstream target genes, and to prevent elastase formation induced by AAA ( Bernal et al, 2020 ); and 7) the severity of skin lesions, autoantibody production, and kidney disease in lupus-associated pathologies ( Sharma et al, 2021 ).…”
Section: Proteomimetics Of Natural Inhibitors Of Jak-statmentioning
confidence: 99%
“…In detail, a preclinical study reported the vasculo-protective action of the SOCS1 mimetic KIR peptide in a mouse model of elastase-induced AAA ( Bernal et al, 2020 ). KIR peptide suppressed STAT1,3 activation in aorta, downregulated cytokines and metalloproteinases, altered the expression of cell differentiation markers, and reduced the incidence of AAA in aortic dilation and elastin degradation.…”
Section: Proteomimetics Of Natural Inhibitors Of Jak-statmentioning
confidence: 99%